Quantum Mechanics MP2 and CASSCF Study of Coordinate Quasi-Double Bonds in Cobalt(II) Complexes as Single Molecule Magnets - Yuemin Liu; Salah S. Massoud; Oleg N. Starovoytov; Tariq Altalhi; Yunxiang Gao; Boris I. Yakobson (Nanomaterials)
Co(II) complexes have shown promising applications as single-molecule magnets (SMMs) in quantum computing and structural biology. Deciphering the Co(II) complexes may facilitate the development of SMM materials. Structural optimizations and calculations of chemical and magnetic properties were performed for Co(II) complexes with a tripodal tetradentate phenolate-amine ligand using MP2/aug-cc-pvdz, MP2/Def2svp, and CASSCF/Def2svp methods. The Second Order Perturbation Theory Analysis of Fock Matrix in NBO Basis unravels that Co(II) ions form unusual coordinate quasi-double bonds with ligand oxygen donor atoms, and the bond strengths range from 142.01 kcal/mol to 167.36 kcal/mol but lack further spectrometric evidence. The average 151.70 kcal/mol of the Co(II-O coordinates quasi-double bonds are formed mainly by two lone pairs of electrons from the ligand phenolate donor oxygen atoms. Dispersion forces contribute 24%, 28%, 27%, and 31% to the Co(II)-ligand interaction. Theoretical results of ZFS D, transversal ZFS E, and g-factor agree well with the experimental values. Magnetic susceptibility parameters calculated based on 5 doublet roots account for 85% of results computed 40 doublet roots are specified. These insights may aid in the rational design of SMM materials and Co(II) porphyrin fullerene conjugate for CO2 electroreduction with superior magnetic properties.